Assessment of the physical environment of epigean invertebrates in a unique habitat: the case of a karst sulfidic spring, Slovenia. Issue 7 (17th December 2014) - Mulec, Janez; Oarga, Andreea; Schiller, Edmund K.; Perşoiu, Aurel; Holko, Ladislav; Šebela, Stanka
Abstract A well‐fissured and faulted karst area at the Žveplenica sulfidic spring created suitable conditions for epigean copepods. Their presence in sulfidic water is a rare phenomenon. To understand the conditions related to sulfidic habitats in the region, two additional springs were analysed: the Studenec karst spring and the Sovra artesian borehole, which contains dissolved sulfide. Water temperature, chemistry and the stable isotopes of oxygen and hydrogen show that the Sovra borehole water has a different origin and history to that of the Žveplenica and Studenec springs water, which is derived from local precipitation. The low slope of the δ18O–δ2H regression line for the Žveplenica spring indicates a mixing of local precipitation water with geothermal sulfidic water that may explain the presence of live copepods. These harpacticoid and cyclopoid copepods must have survived anoxia and high sulfide for some time. The mean transit time for Žveplenica spring cannot be defined precisely from the available data, although the degree of attenuation of the isotopic signal indicates mean transit times of about 1·0 to 1·5 years. Sites similar to Žveplenica spring should be carefully analysed because not only do they provide insights into biodiversity but they also represent an ecotone between the anoxic/oxic and high/low sulfide of these karst waters. Copepods in similar geological settings can be used as additional parameters to evaluate conditions in subsurface sulfidic habitats and their spatial connectivity and responses to hydrological events. Copyright © 2014 John Wiley & Sons, Ltd.